Nuclear energy and bio energy carbon capture and storage, keys for obtaining 1.5°C mean surface temperature limit. (2017) - Berger, André; Blees, Tom; Breon, Francois-Marie; Brook, Barry W.; Deffrennes, Marc; Durand, Bernard; Hansen, Philippe; Huffer, Elisabeth; Grover, Ravi B.; Guet, Claude; Liu, Weiping; Livet, Frederic; et al.
A rapid development of nuclear energy production reaching 173 EJ/y in 2060 and 605 EJ/y in 2110 limits the Global Mean Surface Temperature (GMST) increase to 1.5°C with respect to preindustrial value, with a reduction of the stored carbon dioxide from 800 Gt in the original MESSAGE-Efficiency scenario to 275 Gt in the present one, while multiplying by 6 the Total Primary Energy Supply between 2015 and 2110.